Water Quality Parameters of Buyuk Menderes River, Turkey - YESILIRMAK, ERCAN; ANAC, SUER (Asian Journal of Chemistry, 2010)
In this study, some water quality parameters at 8 sampling stations in Buyuk Menderes river were investigated. These water quality parameters are chemical oxygen demand (COD), electical conductivity (EC), sulphate, chloride, bicarbonate, sodium, potassium, calcium and magnesium. Significance of trends were tested using nonparametric Seasonal Kendall test and trend slopes were quantified using Seasonal Kendall slope estimator. Significant increasing trends at six stations suggested that water quality of Buyuk Menderes river has been deteriorated. It is expected that the results of this study not only will provide public with the recent change in water quality of Buyuk Menderes river quantitatively but also will help establish future management strategies.